Analisis Rasio Keuangan dan Perkembangan Laba Bersih PT Indoritel Makmur TBK Periode 2016-2025: Analysis of Financial Ratios and Net Profit Development of PT Indoritel Makmur Tbk Period 2016-2025 - Kiki Sidabutar; Epi Enjelina; Neisha Fitria; Naila Lubbi; Nova Alisia (PT Cakrawarti Empat Proksi, 2026)
This study seeks to analyze the financial performance of PT Indoritel Makmur Internasional Tbk using financial ratio analysis and net profit growth for the years 2016 to 2025. A descriptive quantitative technique was utilized in the research, which used secondary data from the company's annual financial statements. The Current Ratio (CR), Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and annual net profit growth were all used in the analysis. Throughout the years 2016 to 2021, the firm had comparatively constant financial performance, according to the statistics. Due to the dominance of dividend income, profitability rose significantly in 2022, as indicated by an NPM that was over 100%. In 2023, there was a period of declining performance, with net profit declining by 44.09% and ROA and ROE declining as well. With positive net profit growth, the firm's performance once again increased in 2024 and 2025. In general, the organization showed a great ability to maintain profitability and liquidity despite changing business conditions. The research findings are expected to serve as a basis for evaluation for both company management and investors in assessing the financial performance of investment companies.